DAMPAK FREKUENSI BEROLAHRAGA TERHADAP KESEHATAN MENTAL KARYAWAN DI KOTA MAKASSAR - Muhammad Harliawan; Yudik Prasetyo; Ali Satia Graha (IKIP PGRI Pontianak, 2024)
This research aims to determine the effect of exercise intensity on mental health in PT employees. Ramayana Makassar City The population in this study were all employees of PT. Ramayana Makassar City as many as 74, the sampling technique used was total sampling. The data collection method uses a survey method, while the instruments used are a questionnaire to measure exercise intensity and the Self-Reporting Questionnaire-20 questionnaire to measure the level of mental health. The results of this study are that exercise intensity does not have a significant influence on mental health with a significant level of influence of intensity. There is no significant influence of exercise on mental health based on the SPSS output. The significance level (sig) of the exercise intensity variable (X) is 0.340, because the sig value. 0.340 > probability of 0.05, so there is no significant influence on the exercise intensity variable on employee mental health, there are several factors that are considered to be triggers for employees to be categorized as mental stress levels at work, imbalance between work and life, lack of social support at work, and pressure at work